Exploring complex pheromone biosynthetic processes in the bumblebee male labial gland by RNA sequencing - Buček, A; Brabcová, J; Vogel, H; Prchalová, D; Kindl, J; Valterová, I; Pichová, I (Insect molecular biology, 2016)
Male marking pheromones (MPs) are used by the majority of bumblebee species (Hymenoptera: Apidae), including a commercially important greenhouse pollinator, the buff-tailed bumblebee (Bombus terrestris), to attract conspecific females. MP biosynthetic processes in the cephalic part of the bumblebee male labial gland (LG) are of extraordinary complexity, involving enzymes of fatty acid and isoprenoid biosynthesis, which jointly produce more than 50 compounds. We employed a differential transcriptomic approach to identify candidate genes involved in MP biosynthesis by sequencing Bombus terrestris LG and fat body (FB) transcriptomes. We identified 12 454 abundantly expressed gene products (reads per kilobase of exon model per million mapped reads value > 1) that had significant hits in the GenBank nonredundant database. Of these, 876 were upregulated in the LG (> 4-fold difference). We identified more than 140 candidate genes potentially involved in MP biosynthesis, including esterases, fatty acid reductases, lipases, enzymes involved in limited fatty acid chain shortening, neuropeptide receptors and enzymes involved in biosynthesis of triacylglycerols, isoprenoids and fatty acids. For selected candidates, we confirmed their abundant expression in LG using quantitative real-time reverse transcription-PCR (qRT-PCR). Our study shows that the Bombus terrestris LG transcriptome reflects both fatty acid and isoprenoid MP biosynthetic processes and identifies rational gene targets for future studies to disentangle the molecular basis of MP biosynthesis. Additionally, LG and FB transcriptomes enrich the available transcriptomic resources for Bombus terrestris.
Keywords: Animals; sekvenční analýza RNA; apoptóza; mastné kyseliny; tukové těleso; apoptosis; hydrolýza; polymerázová řetězová reakce; terpeny; Fat Body; Bombus terrestris; Polymerase Chain Reaction; Fatty Acids; Apoptosis; sekvence aminokyselin; Molecular Sequence Data; Terpenes; Lipid Metabolism; Amino Acid Sequence; metabolismus lipidů; marking pheromone biosynthesis; aldehydoxidoreduktasy; RNA-seq; molekulární sekvence - údaje; Male; labial gland; Fatty Acid Desaturases; Hydrolysis; transcriptome; Bees; Aldehyde Oxidoreductases; včely; transkriptom; Pheromones; zvířata; mužské pohlaví; desaturasy mastných kyselin; Transcriptome; feromony; Sequence Analysis, RNA